Preschool Suspension and Expulsion for Young Children With Disabilities. (January 2021) - Zeng, Songtian; Pereira, Brittany; Larson, Anne; Corr, Catherine P.; O'Grady, Courtney; Stone-MacDonald, Angi
Despite their negative effect, preschool suspension and expulsion are prevalent. Researchers have explored adverse childhood experiences and teachers' racial bias that link to disproportionate suspension and expulsion in preschools, but little research has investigated disability status as a risk factor. This study investigates the extent to which preschool children with disabilities are related to exclusionary practices. We used weighted logistic regression to analyze data from the 2016 National Survey of Children's Health. Results indicated that 5.4% of young children with disabilities had been either suspended or expelled, compared to 1.2% of children without disabilities. Accounting for child- and family-level covariates, disability status was not a strong indicator of preschool suspension or expulsion. Instead, young children with attention deficit disorder or attention deficit hyperactivity disorder or reported behavioral or conduct problems were much more likely to experience exclusionary practices. Implications for prevention and response efforts to address challenging behavior and promote inclusive practices in preschool settings for all children are discussed.